2004
DOI: 10.1002/jcb.20359
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional comparison of 1,25‐dihydroxyvitamin D3 and the novel vitamin D receptor ligand, lithocholic acid, in activating transcription of cytochrome P450 3A4

Abstract: The vitamin D receptor (VDR) binds to and mediates the effects of the 1,25-dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) hormone to alter gene transcription. A newly recognized VDR ligand is the carcinogenic bile acid, lithocholic acid (LCA). We demonstrate that, in HT-29 colon cancer cells, both LCA and 1,25(OH)(2)D(3) induce expression of cytochrome P450 3A4 (CYP3A4), an enzyme involved in cellular detoxification. We also show that LCA-VDR stimulates transcription of gene reporter constructs containing DR3 and ER6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 100 publications
10
67
0
Order By: Relevance
“…2A). In the case of VDR, this observation could be explained based on the different recruitment of coactivators to VDR by 1,25OHvitD 3 and LCA [37]. In support of this, the structure-function relationships of VDR and LCA revealed that LCA interacts with different amino acids in the ligand binding domain (LBD) of VDR in comparison with 1,25OHvitD 3 [38,39].…”
Section: Discussionmentioning
confidence: 90%
“…2A). In the case of VDR, this observation could be explained based on the different recruitment of coactivators to VDR by 1,25OHvitD 3 and LCA [37]. In support of this, the structure-function relationships of VDR and LCA revealed that LCA interacts with different amino acids in the ligand binding domain (LBD) of VDR in comparison with 1,25OHvitD 3 [38,39].…”
Section: Discussionmentioning
confidence: 90%
“…However, Cyp27a1-null mice showed a normal phenotype in the vitamin D activation pathway (15). Over the years, the identification of the nuclear hormone response elements in the Cyp3a4 gene promoter has drawn attention to the most abundant P450 in human liver and intestine as a possible vitamin D 25-hydroxylase (46)(47)(48)(49)(50), although the vitamin D receptor is undetectable in the liver (51). CYP3A4 is a well-known xenobiotic-metabolizing enzyme and can act on approximately half of the drugs in use.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that LCA enters the colonic enterocyte, activates VDR, and thereby induces its own detoxifi cation ( 15 ). LCA was also shown to induce hepatic CYP3A4, a target gene regulated by VDR that is involved in bile acid metabolism, notably the oxidation of bile acids ( 16 ).…”
Section: Metabolomics Analysis Of Urine Bile and Tissue Homogenatesmentioning
confidence: 99%